Ovarian Carcinosarcoma and Its Association with Mature Cystic Teratoma and Primary Tubal Carcinoma - Sunida Rewsuwan; Nopporn Satabongkoch; Prapaporn Suprasert; Surapan Khunamornpong (Case Reports in Pathology)
Introduction. Carcinosarcoma is an uncommon form of ovarian cancers, classified as being part of the group of mixed epithelial and mesenchymal tumors. The occurrence of carcinosarcoma in association with a mature cystic teratoma and synchronous tubal carcinoma is very rare. Case Report. A 69-year-old woman presented with a pelvic mass. An abdominal computerized tomographic scan detected a 15 cm right pelvic mass which was suggestive of malignant transformation of a dermoid cyst. Intraoperative, bilateral ovarian masses (left 10 cm and right 12 cm) with diffuse peritoneal metastatic nodules were identified. Histologically, the left ovarian mass was composed of 2 components including carcinosarcoma and mature cystic teratoma, whereas the right ovarian mass represented a mature cystic teratoma with serosal surface involvement of high-grade serous adenocarcinoma. The left fallopian tube was macroscopically unremarkable but contained a 5.0 mm focus of high-grade serous adenocarcinoma in the distal part, with adjacent serous tubal intraepithelial carcinoma. Conclusion. As the fallopian tube has recently been proposed to be an origin for a majority of pelvic or ovarian high-grade serous adenocarcinomas, tubal carcinoma may be the origin for ovarian carcinosarcomas through an epithelial-mesenchymal transition. The coexistence of ovarian carcinosarcoma and teratoma in the present case should represent a collision tumor.